Leadership Lessons from Dr Pritam Singh - Ltd, SAGE Publications India Pvt (SAGE back to basics, 2021)
'Leadership can never be taught through cases and lectures alone.'A Padma Shri awardee and a role model for CEOs and students alike, Late Dr Pritam Singh words, 'I look at the crisis of leadership as a global crisis' rings truer today than ever. Leadership Lessons from Dr Pritam Singh is a testament to the author's exemplary work in leadership and management education, and a way forward for new-age leaders and CEOs struggling to move beyond general management and administration. The book consists of cases and ideas on leadership practised and espoused by the late author throughout his reputable career and life.SAGE Back to Basics is a distilled compilation of proven and timeless ideas and best practices for new-age and experienced leaders alike. The hand-picked collection of books-on management, leadership, entrepreneurship, branding and CSR-offer advice from management experts whose knowledge and research has impacted and shaped business and management education. Other books in the series:Timeless Leadership | Advertising and Branding Basics | Corporate Social Responsibility in India | Basics of Entrepreneurship | Human Resource Development Insights | Ideate, Brainstorm, Create | Building Professional | Timeless Management | Soft Skills for Workplace Success